Dental anomalies in children submitted to antineoplastic therapy - Carrillo, Camila Merida; Pires Correa, Fernanda Nahas; Fontana Lopes, Nilza Nelly; Fava, Marcelo [UNESP]; Odone Filho, Vicente (Universidade de São Paulo (USP), Hospital das Clínicas, 2014)
Cancer is the third most frequent cause of death in children in Brazil. Early diagnosis and medical advances have significantly improved treatment outcomes, which has resulted in higher survival rates and the management of late side effects has become increasingly important in caring for these patients. Dental abnormalities are commonly observed as late effects of antineoplastic therapy in the oral cavity. The incidence and severity of the dental abnormalities depend on the child's age at diagnosis and the type of chemotherapeutic agent used, as well as the irradiation dose and area. The treatment duration and aggressivity should also be considered. Disturbances in dental development are characterized by changes in shape, number and root development. Enamel anomalies, such as discoloration, opacities and hypoplasia are also observed in these patients. When severe, these abnormalities can cause functional and esthetic sequelae that have an impact on the children's and adolescents' quality of life. General dentists and pediatric dentists should understand these dental abnormalities and how to identify them aiming for early diagnosis and appropriate treatment.
Keywords: Tooth Abnormalities; Drug/Radiotherapy; Cancer; Child